(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
The transportation and localization of technologies is considered a rather important issue, especially the ones that benefits the economy, of which is the development and fabrication of LASER systems of all kinds, the laser devises income has estimated to be 6 million a year, and the optic communication laser has the highest percentage of 31% of the market annual share. this research aimed to the precise knowledge and understanding of the technology of rare earths doped single-mode optical-fiber lasers as a gain medium by performing an accurate literature review through setting a novel way included in the text below. Er-doped LUCENT HP980 optical fiber is chosed as a gain medium, and we have reached a gain medium using Optisystem as a simulator, which is used by optics tech companies and research centers across the glope, for the simulator has database includes all the essential optical elements to build an important optical system hence, this research according to the HP980 simulation results has proposed a laser system that release at constant power (-5dm) at (λi=1531.8nm+3.2i ; i=0,1,2,3) for the purpose of optic communications that fulfill the demands and recommendations of ITU-U and Wavelength Division Multiplexing.